Social Studies-Specific Field Skills Acquired by Primary School Students in the Process of Virtual Museum Education - Erol, Mustafa; Erol, Ahmet; Ozdemir, Fatih (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This study focuses on how virtual museum education (VME) can support elementary school students' social studies-specific domain skills (spatial perception, using evidence, location analysis, perceiving change and continuity, and perceiving time and chronology). For this purpose, the study was conducted using action research, one of the qualitative research traditions. The study participants consisted of fourth-grade students selected by convenience sampling. Data were collected through a pre-intervention interview form, a post-intervention interview form, an observation form, and student drawings. In this context, students participated in virtual museum training, one museum per week for seven weeks. The data obtained were analyzed using content analysis. According to the findings, VME improved students' using evidence, location analysis and spatial perception. Additionally, VME contributed to students' understanding of perceiving change and continuity and a deeper understanding of perceiving time and chronology. Therefore, these immersive experiences effectively help students acquire social studies skills.
Keywords: Virtual museums; social studies; specific field skills; primary school; museum education; TRIPS; Education & Educational Research